PEG-induced physiological drought for screening winter wheat genotypes sensitivity – integrated biochemical and chlorophyll a fluorescence analysis - Peršić, Vesna; Ament, Anita; Antunović Dunić, Jasenka; Drezner, Georg; Cesar, Vera (Frontiers in Plant Science, 2022)
To apprehend possible adaptive features of drought tolerance in different winter wheat genotypes, this study included: visual, morphological (root to shoot ratio), biochemical (pigment content, lipid peroxidation, proline content), and physiological (membrane stability, chlorophyll-a fluorescence) measurements in the first phase of seedlings growth (10 days old seedlings) exposed to a type of stress that was not a typical drought (in terms of deprivation of watering) but a physiological depletion (induced by PEG-6000) of a strength corresponding to mild stress (ψ = −0.3 MPa) well within physiological limits. The goal was to screen genotypes at the onset of metabolic changes induced by water deficit for impact on photosynthetic apparatus function and structure. The results indicated that drought treatment was the most influential variable affecting plant growth and relative water content, while genotype variability determines with what intensity varieties of winter wheat seedlings responded to drought. PCA analysis considering all data for control and treatment showed that PEG-induced drought changed phenomenological energy fluxes and the efficiency with which an electron is transferred to final PSI acceptors. Fluorescence parameters that accurately described tested genotypes based on the effect size were grouped as follows: photochemical parameters (PC1) representing the donor and acceptor side of PSII; thermal phase of the photosynthetic process (PC2) and the acceptor side of PSI, representing the electron flow around PSI and the chain of electrons between PSII and PSI, and phenomenological energy fluxes per cross-section (PC3). Four distinct clusters of genotypes were discerned based on their response to imposed physiological drought, and integrated analysis enabled an explanation of their reactions' specificity. The most reliable parameters of the JIP-test in detecting and comparing the drought impact among tested genotypes were variable fluorescence at K, L, and I step and PITOT. Multivariate analyses and data mining of all parameters after stress enabled the exploration of physiological processes in all genotypes, thus complementing the knowledge needed to address fundamental issues, like plasticity, in young and fully developed plants.